The Impact of Mergers and Acquisitions on Shareholders’ Value : An Empirical Analysis of Select Indian Companies - Prakash, Shree (Indian Journal of Finance, 2017)
The present study analyzed the shareholder value creation by examining the short-run abnormal returns accruing to the shareholders of acquiring, target, and hypothetical combined entities on announcement of mergers and acquisitions (M&As) during 2000 - 2010 using the market-adjusted model of the popular event study methodology. This study used a sample of 29 pairs of acquiring and target firms involved in M&As during the period from April 1, 2000 to March 31, 2010. The study developed four hypotheses examining separately the impact of M&As on shareholder value of acquiring, target, and combined firms. The study reported little but significant positive abnormal returns accruing to the shareholders of acquiring firms, while shareholders of target firms were found to have suffered significant losses over a 41-day event period around the announcement of M&As, which is contrary to existing literature in Western countries, which has stated that only the targets create value, and the acquirers are value destructive. This is an important contribution to the existing literature that the theories in the Western countries may not necessarily hold valid in India, and they need to be reassessed before being implemented in the Indian context. Another important findings of the study was that M&As overall were found destroying value for the shareholders of the hypothetical combined entity.